(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article provides a comprehensive analysis of the role and impact of mass media in modern society. It explores how mass media has evolved over time and become an essential part of everyday life. The paper discusses various types of media, including traditional and digital platforms, and evaluates their advantages and disadvantages. Special attention is given to the influence of social media, the role of media in shaping public opinion, and its impact on culture and education. Furthermore, the study highlights the importance of media literacy and critical thinking in the digital age. The findings indicate that mass media is a powerful tool that can both positively and negatively affect society, depending on how it is used.